Productive arts engagement at the Tokyo Fuji Art Museum and its health effects on the older Japanese population: results of a randomized controlled trial - Hayashi, Yoko; Matskiv, Jacqueline; Galery, Kevin; Beauchet, Olivier (Frontiers in Medicine, 2023)
Background: This randomized controlled trial aims to compare changes in mental and physical health in older Japanese community-dwellers who participated in a productive art-based activity at the Tokyo Fuji Art Museum (intervention group) and in their counterparts, who did not participate in the intervention (control group). Methods: A total of 73 older community-dwellers living in Tokyo participated in a single-blind RCT in two parallel groups (intervention group versus control group). The intervention was 2 hours of productive art-based activities per week. The weekly sessions were carried out at the Tokyo Fuji Art Museum over a 12-week period. The control group did not participate in any productive art-based activity over the study period. Well-being, quality of life and frailty were assessed before the first and after the last productive art-based activity. These outcomes were assessed with the same schedule in both groups. Results: There was a significant improvement of quality of life (P=0.003) and of physical health (i.e., decreased frailty status) (P=0.014) in the intervention group compared to the control group. No conclusive effect was shown with well-being. Interpretation: This RCT showed mixed health effects of productive art engagement in older Japanese community-dwellers in Tokyo. Benefits were reported for quality of life and frailty but no significant effect was found for well-being.